Identifikasi Pabrik Gula Sebagai Industrial Heritage Di Jawa - Nugroho, Purwanto Setyo (Universitas Sebelas Maret Surakarta, 2020)
Sugar Factory is a historical marker of the entry of modern industrialization in Java, the existence of a sugar factory is also a witness to the triumph of the sugar industry in Java which was once the second largest sugar supplier in the world. Sugar mills have certain architectural forms and functions, and are recognized as important architectural heritage. This study aims to identify the existence of sugar factories that once existed in Java, and look for aspects related to the importance of sugar factories as industrial heritage with qualitative descriptive methods. Research findings are expected to be useful for conservation preservation activities. The identification results show there are about 231 sugar factories that have ever existed in Java. At present, only 45 factories are still active. Most active sugar mills are located in East Java. Identification that can lead to the determination of the importance of sugar factories as industrial heritage can be seen from the aspects of location, age, function, ownership, physical condition, architectural style and historical events associated with it.